Recent developments and experimental guidelines in mobile ad-hoc networks. (10th May 2010) - Dow, C.R.; Lin, P.J.; Chen, S.C.; Lin, J.H.; , S.F. Hwang
The Mobile Ad-hoc Network (MANET) is one of the most vibrant and active current research topics. This work investigates and analyses recent research trends and presents experimental guidelines on MANETs. More than 1900 MANET-related papers were collected and surveyed in IEEE/IEE Electronic Library (IEL Online) from 1998 to 2004. The research trends, qualitative analysis and simulation guidelines from 15 major MANET issues are investigated to assist the user in conducting MANET research. On the basis of recent seven-year trends, we found that some issues, such as routing, power management and bandwidth management, have attracted much attention. We also found that some issues have potential study values, such as radio interface and security. In the qualitative analysis, we found that some factors such as scalability, stability and reliability attracted much attention in major MANET issues. The essential simulation metrics for various MANET issues are identified and listed for experimental guidelines. The analysis results also demonstrate the utilisation trends for various MANET simulators.